Learner support system and academic performance of distance learning students in selected Kenyan public universities (Teacher Education through Flexible Learning in Africa (TETFLE), 2021)
Distance learning is a mode of study globally accepted as a tool for enhancing access, equity and quality in education. The Kenyan Government has put in place mechanisms to promote open and distance learning practices in educational institutions. However, there is doubt in Kenya, regarding the quality of academic performance attained by distance learning students. The objective of this study was to determine the influence of learner support systems on the academic performance of distance learning students in selected Kenyan public universities. The study is based on Pragmatism due to its focus on objectivity and the use of scientific methods. Mixed-methods research methodology was adopted for the study. The sample consisted of 847 Bachelor of Education (Arts) distance learning students, 149 lecturers teaching distance learning students, and two (2) administrators in charge of distance learning programmes. The research instruments consisted of questionnaires, interview guides, document analysis and the instrument for measuring academic performance. The findings indicated that a learner support system statistically, significantly and positively influences academic performance of distance learning students, although at a low level (4.9%). However, the findings revealed that guidance and counselling support, which is part of the learner support system, did not significantly influence the academic performance of distance learning students. The study recommends that particular focus should be on the provision of remotely accessible guidance and counselling services since most distance learning students cannot physically access the services which are on campuses.
Keywords: Distance learning; learner support system; academic performance